Microwave-induced Apoptosis and Cytotoxicity of NK Cells through ERK1/2 Signaling - ZHAO, Li; LI, Jing; HAO, Yan Hui; GAO, Ya Bing; WANG, Shui Ming; ZHANG, Jing; DONG, Ji; ZHOU, Hong Mei; LIU, Shu Chen; PENG, Rui Yun (Biomedical and environmental sciences, 2017)
Objective To investigate microwave-induced morphological and functional injury of natural killer（NK） cells and uncover their mechanisms. Methods NK-92 cells were exposed to 10, 30, and 50 m W/cm~2 microwaves for 5 min. Ultrastructural changes, cellular apoptosis and cell cycle regulation were detected at 1 h and 24 h after exposure. Cytotoxic activity was assayed at 1 h after exposure, while perforin and NKG2 D expression were detected at 1 h, 6 h, and 12 h after exposure. To clarify the mechanisms, phosphorylated ERK（p-ERK） was detected at 1 h after exposure. Moreover, microwave-induced cellular apoptosis and cell cycle regulation were analyzed after blockade of ERK signaling by using U0126. Results Microwave-induced morphological and ultrastructural injury, dose-dependent apoptosis（P 〈 0.001） and cell cycle arrest（P 〈 0.001） were detected at 1 h after microwave exposure. Moreover, significant apoptosis was still detected at 24 h after 50 m W/cm~2 microwave exposure（P 〈 0.01）. In the 30 m W/cm~2 microwave exposure model, microwaves impaired the cytotoxic activity of NK-92 cells at 1 h and down regulated perforin protein both at 1 h and 6 h after exposure（P 〈 0.05）. Furthermore, p-ERK was down regulated at 1 h after exposure（P 〈 0.05）, while ERK blockade significantly promoted microwave-induced apoptosis（P 〈 0.05） and downregulation of perforin（P 〈 0.01）. Conclusion Microwave dose-dependently induced morphological and functional injury in NK-92 cells, possibly through ERK-mediated regulation of apoptosis and perforin expression.